ANTIBACTERIAL ACTIVITY of GARLIC (Allium sativum l.) - Salima, Jeanna (Majority, 2015)
Abstract Infectious disease has become one of the most major health concern not only in Indonesia, but also around the world. Antibiotics is one way of treating infectious disease which, if it was given irrationally, could lead into a whole new problem, which is the presence of a resistant pathogen. Therefore, a new kind of treatment using various kind of herbal medicine is now widely used. Garlic has been widely known for its potency of dietary and medicinal use to cure many various diseases, including infectious disease, for centuries. It is a large annual plant of the Liliaceae family. One of many benefits from garlic potency in medicinal term that has long been studied by many clinician is its possession of antibacterial properties. There are a lot of researches stated that various extract of garlic shows an excellent antibacterial activity against some human pathogenic bacteria. The antibacterial activity of garlic extracts has a broad spectrum, this, shown by its ability to inhibits both gram negative and gram positive bacteria. This antibacterial activity possessed by extraction of garlic is believed due to one of its phytochemical constituent, allicin, which is one of major organo sulfur contained in garlic bulb, and its degradation, ajoene. It is also believed that gram positive bacteri as are more susceptible to antibacterial activity of garlic extract than gram negative bacteries. Garlic also contains flavonoid and essentials oil, which also has antibacterial activity. Keyword: antibacterial activity, garlic extract, Staphylococcus aureus. Abstrak Penyakit infeksi telah menjadi salah satu masalah kesehatan terbesar, tidak hanya di Indonesia tapi juga di dunia.Pemberian antibiotic, telah lama menjadi salah satu terapi dalam menyembuhkan penyakit infeksi, namun, apabila pemberian antibiotic tidak dilakukan secara rasional, hal ini dapat menimbulkan masalah baru, yaitu munculnya patogen yang bersifat resisten.Oleh karena itu, pengobatan alternative dengan menggunakan bahan dan tanaman herbal sekarang banyak digunakan.Bawang putih sudah berabad-abad lamanya dikenal memiliki potensi medis dan dipercaya dapat berperan sebagai obat herbal yang dapat digunakan untuk berbagai macam penyakit, termasuk penyakit infeksi.Tanaman bawang putih merupakan salah satu herba semusim famili Liliceae.Salah satu manfaat medis bawang putih yang telah lama dipelajari oleh para klinisi ialah kemampuan atau potensi bawang putih sebagai antibiotik.Sudah banyak peneltian menyatakan bahwa ekstrak bawang putih dengan efektif menunjukkan aktivitas yang baik terhadap bayak jenis bakteri, baik itu bakteri gram negatif ataupun gram positif.Hal ini menjadikan ekstrak bawang putih memiliki sifat antibakteri berspektrum luas.Aktivitas antibakteri ini diyakini dikarenakan kandungan allicindan ajoene, sebuah komponen organosulfur yang dimiliki oleh bawang putih.Dipercaya pula bahwa bakteri gram positif lebih rentan terhadap aktivitas antibakteri yang dimiliki oleh ekstrak bawang putih.Selain itu, bawang putih juga memiliki kandungan flavonoid dan minyak atsiri yang juga mempunyai aktivitas antibakteri. Kata kunci: aktivitas antibakteri, ekstrak bawang putih,Staphylococcus aureus